MODEL LAJU PENGERINGAN SPAGHETTI JAGUNG MENGGUNAKAN TRAY DRIER - Tjahja Muhandri; Gina Nur Rahmasari; Subarna -; Purwiyatno Hariyadi (Jurnal Teknologi dan Industri Pangan, 2015)
Drying is the most crucial process that determine the final quality of pasta products. In this case, drying at high temperature has been widely used. However, it allows texture damage in the form of cracking in the product. Drying model can be used in drying process control to prevent such kind of damage and also to design the optimum condition. The objective of this research is to determine drying model of corn spaghetti using tray drier. In this study, drying was performed at three levels of air velocity (1.29; 0.90; and 0.49 m/s), three levels of instrument temperature setting (6, 8, and 10), and two setting of drying position (vertical and horizontal to the airflow). Results indicated that drying temperature was the most influencing parameter in corn spaghetti drying. It also could be concluded that drying rate of corn spaghetti could be well represented by thin layer drying equation (Page model).